1988
DOI: 10.2307/2008585
|View full text |Cite
|
Sign up to set email alerts
|

On Secant Updates for Use in General Constrained Optimization

Abstract: Abstract.In this paper we present two new classes of successive quadratic programming (SQP) secant methods for the equality-constrained optimization problem. One class of methods uses the SQP augmented Lagrangian formulation, while the other class uses the SQP Lagrangian formulation.We demonstrate, under the standard assumptions, that in both cases the BFGS and DFP versions of the algorithm are locally q-superlinearly convergent. To our knowledge this is the first time that either local or (j-superlinear conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…If t*k]lPkgkll < Ak, then ~ = --t*kPkgk is a feasible solution of problem (Sk), and hence t* ~k < 0k (~) = Ck (k) 1 IIPkgkll ~…”
Section: T~ --= ( Pkgk ) T ( Pk Bk Pk )( Pkgk )mentioning
confidence: 99%
See 3 more Smart Citations
“…If t*k]lPkgkll < Ak, then ~ = --t*kPkgk is a feasible solution of problem (Sk), and hence t* ~k < 0k (~) = Ck (k) 1 IIPkgkll ~…”
Section: T~ --= ( Pkgk ) T ( Pk Bk Pk )( Pkgk )mentioning
confidence: 99%
“…For the cla~s of constrained nonlinear optimization problem min f(x) (1) s.t. c(x) ~= (Cl(X),...,Cm(X)) =0…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Powell (1985) has noted that his (1977) strategy may in fact produce badly conditioned matrices and the same may be true of (28)-(31). Other authors, including Pantoja (1984), Tapia (1984) and BartholomewBiggs (1985), have suggested alternative updating schemes which appear promising and which may, in due course, supersede both the techniques mentioned above.…”
Section: B(k)d = Tr(atu-f) and Dtb(k)d = O'2pt(atu-f);mentioning
confidence: 99%